INDUSTRIAL ENTERPRISES BY BANKS PROBLEMS OF LOANING AND WAYS TO SOLVE THEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Investment loans of commercial banks are an important source of financing the costs of modernization, technical and technological re-equipment of industrial enterprises. However, banks need to have sufficient resources to increase the use of investment loans by commercial banks, while industrial enterprises need to be able to repay investment loans in a timely and complete manner. The article identifies current issues related to the improvement of lending practices of industrial enterprises of commercial banks of the Republic of Uzbekistan, and develops scientific proposals to address them.